If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9-(2x+1)*3-4(x+5)=-4
We simplify the equation to the form, which is simple to understand
9-(2x+1)*3-4(x+5)=-4
Reorder the terms in parentheses
9-(+6x+3)-4*(x+5)=-4
Remove unnecessary parentheses
9-6x-3-4*(x+5)=-4
Reorder the terms in parentheses
9-6x-3+(-4x-20)=-4
Remove unnecessary parentheses
+9-6x-3-4x-20=-4
We move all terms containing x to the left and all other terms to the right.
-6x-4x=-4-9+3+20
We simplify left and right side of the equation.
-10x=+10
We divide both sides of the equation by -10 to get x.
x=-1
| 2(x+4)+5=17 | | 7(x+2)-6(x-3)=24 | | 4-5(x+11)=20+2(3-4x) | | 131+155x=155 | | 131+150x=150 | | 131+.21x=x | | 50=1.8c+32 | | 3(x+8)+2=9x+8 | | 131+.24x=x | | 22=.5b(8) | | 2/3a^2=13 | | 3w+10=35 | | 4x^2-36x^2=0 | | 2/5+3/4-1/2= | | 2w+5(4)=60 | | 36x^2-y^2= | | -0.1417x^2+23.365x=946.12 | | 5+.25=13 | | 3x^2-4=503 | | 3(x-1)*(x-1)+4x-4=0 | | 3(x-1)+4x-4=0 | | 17-x=2x+5 | | e=g+p/2 | | 3x+7-x=11 | | 15=2x+3x+5 | | x-5-2x=9 | | h+26.9=8.27 | | 41/2x23/4 | | 2x^2+7x-10=5x^2-10 | | 4x^2+6x=8-2x | | a(a+bc)+cb+ab+ac-3x(ab-cb-ba+bc)= | | 4x-(9-x)=x+7 |